2011
DOI: 10.5402/2011/137637
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Inhibiting Activity of Some 4-Hydroxycoumarin Derivatives on HIV-1 Protease

Abstract: Six novel 4-hydroxycoumarin derivatives were rationally synthesized, verified, and characterized by molecular docking using crystal HIV-1 protease. Molecular docking studies predicted antiprotease activity of (7) and (10). The most significant functional groups, responsible for the interaction with HIV-1 protease by hydrogen bonds formation are pyran oxygen, atom, lactone carbonyl oxygen and one of the hydroxyl groups. The newly synthesized compounds were biologically tested in MT-4 cells for inhibiting HIV-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The highest inhibition of HIV-1 PR (25%) and highest MT4 cell survival (78%) were demonstrated by compound containing m-nitrophenyl derivative (44) ( Fig. 10) [40].…”
Section: Introductionmentioning
confidence: 99%
“…The highest inhibition of HIV-1 PR (25%) and highest MT4 cell survival (78%) were demonstrated by compound containing m-nitrophenyl derivative (44) ( Fig. 10) [40].…”
Section: Introductionmentioning
confidence: 99%
“…A number of comparative studies have shown scavenging effect of coumarins against reactive oxygen species (ROS) and their potential anti‐inflammatory activity, particularly in the treatment of inflammatory bowel disease (IBD) . Compounds containing coumarin moiety have also been reported to have an inhibition effect towards lipidic peroxidation, prostaglandin biosynthesis, and HIV‐1 PR …”
Section: Introductionmentioning
confidence: 99%
“…[13] Compounds containing coumarin moiety have also been reported to have an inhibition effect towards lipidic peroxidation, prostaglandin biosynthesis, [13] and HIV-1 PR. [14] In many studies, the substitutions at C-3 and C-4 of the coumarin nucleus resulted in improved biological activity, such as the cytotoxic and anti-inflammatory potency, [9,15,16] compared to the simple coumarin molecule. For example, in recent works [17,18] synthesis of some substituted coumarin derivatives bearing a thiazole or pyrazole unit have been reported to possess antimicrobial, analgesic and anti-inflammatory activities (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, 4-hydroxycoumarin and its derivatives have drawn much attention due to their wide range of pharmacological effects. Many of them exhibit other important pharmacological properties, including antipyretic and antinociceptive 12 , anti-inflammatory [13][14] , antibacterial 15 , anti-viral 16 , anti-HIV 17 , antioxidant 18 and anti-cancer 19 effects. Thus, the goal of this work was to evaluate the relationship between the structure and the radical scavenging activity of synthetic 3-substituted-4-hydroxycoumarins, namely 3-acetyl-4-hydroxycoumarin, 3-ethoxycarbonyl-4-hydroxycoumarin and 3-acetylphenylhydrazone-4-hydroxycoumarin, in comparison to 4-hydroxycoumarin and BHT used as references (table 1).…”
Section: Introductionmentioning
confidence: 99%